Al-Muhafadzah bil Qadim al-Shalih wa Al-Akhdzu bil Jadid Al-Ashlah in Education Perspective of Hadrotus Syaikh KH Hasyim Asy'ari - Intan Nur Aini; Imam Sopingi; Athi’ Hidayati (Islamic Religious Education Master Program Universitas Islam Internasional Darullughah Wadda'wah, 2025)
This study explores the educational thought of Hadrotus Syaikh KH. Hasyim Asy'ari, the founder of Nahdlatul Ulama, through the principle of al-muhafadzah ‘ala al-qadim al-shalih wa al-akhdzu bil jadid al-ashlah—preserving noble traditions while embracing beneficial innovations. The research aims to examine how this principle informs Islamic educational practices and its relevance in modern contexts. Employing a qualitative method through library research, the study analyzes KH. Hasyim Asy’ari’s primary works, especially Adab al-‘Alim wa al-Muta‘allim, and secondary sources discussing Islamic education. The findings reveal that KH. Hasyim Asy'ari emphasized education not merely as knowledge transfer, but as a process of moral, spiritual, and character formation grounded in Islamic values such as justice, humility, sincerity, and honesty. He advocated balancing religious and general sciences and urged educators to serve as moral exemplars. This research contributes to the discourse on Islamic education by offering a classical yet adaptive framework rooted in tradition but open to innovation—providing a model for addressing current educational challenges with strong spiritual foundations and cultural relevance.